Improving Women's Reproductive Health Through Complementary Midwifery: Menstrual Well-being Education and Digital-Based Holistic Therapy - Wahyuni, Candra; Nita Dwi Astikasari; Retno Palupi Yoni Siwi (Link Jurnal Masyarakat, 2025)
Introduction: Menstruation is a physical symptom that occurs in women of reproductive age and can have an impact on daily life. Menstrual Wellbeing Education and Digital-Based Holistic Therapy uses an innovative approach to support women's health and well-being through digital technology. These therapies touch on physical, emotional, and mental aspects by utilizing digital platforms such as applications, videos, and virtual consultations. Objective: to increase women's knowledge and understanding of menstrual cycles, hormonal changes, common symptoms, and pain and emotional management. This approach also seeks to reduce stigma and myths related to menstruation. Methods: This activity consists of a pre-test before counseling, followed by perception with participants, educational stages with the viewing of an educational video, providing information on examples of digital media, such as mobile applications, social media, websites, and virtual consultations. Results: This counseling activity has a positive impact and achieves goals in the form of increasing knowledge, changing attitudes, and promoting more positive behaviors. Conclusion: Digital health products, and in particular menstrual health apps, have the potential to make a positive difference due to their scalability and ease of access